Optimizing Bilingual Learning to Improve Students' Critical Thinking Skills Through PheT Media - Nyak Umi Anggiani; Susanna Susanna; Abdul Hamid; Musdar Musdar (Universitas Syiah Kuala, 2022)
Optimizing bilingual learning through PheT media is one of the conscious efforts of teachers to improve students' critical thinking skills. This study aims to optimize bilingual learning using Phet's media on the critical thinking skills of class XI students at SMA Teuku Nyak Arif Fatih Bilingual School. This type of research is quasi-experimental that uses a nonequivalent control group design model. The population in this study was all class XI which amounted to 2 classes. The sample in this study was taken using a total sampling technique, namely the number of samples equal to the total population of 36 students. The data collection technique used is pretest and posttest learning outcomes tests. The data analysis technique used a two-party t-test with the normality test and homogeneity test first as a prerequisite for the analysis. The results obtained based on data analysis using a two-party t-test, namely - . So according to the hypothesis then is accepted and is rejected, it can be concluded that bilingual learning using PheT media is not optimal to improve the critical thinking skills of students at SMA Teuku Nyak Arif Fatih Bilingual School.